(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The present article is devoted to analysis of the English paremiological units of the components “good” / “bad”. The author finds out the Uzbek analogues to such proverbs. English proverbs which don’t have Uzbek analogues were investigated from linguo-cultural point of view.